KANDUNGAN KROMIUM (Cr) PADA GONDANG (Pila scutata) DI PERAIRAN SUNGAI RIAM KANAN KABUPATEN BANJAR - Aditya Rahman (Bioscientiae, 2012)
Around Riam Kanan river, one can find mining activities and local housing. It ispredicted that those activities might generate waste contaminated with Cr, a toxic heavymetal. In this research, gondang snails (Pila scutata) were used as bioindikator to studyCr pollution in Riam Kanan area. The samples of gondang were taken from 4 stationsalong Riam Kanan, which is 2 kms from reservoir Riam Kanan, Awang Bangkal West,Mandikapau East and Karang Intan Dam. Chromium contents in the gondang samples,sediment and water bodies were analyzed Atomic Absorption Spectrophotometer. Theresult then is correlation regression SPSS version 17. Chromium content at samplegondang is some station of protactinium Cr has in concentration that is enough is height.Result of analysis shows content Cr in water territory ranges from 0,0182-0,0516 ppm,content Cr at sediment ranges from 0,1978-13,8739 ppm and at gondang (Pila scutata) inwater territory of Riam Kanan river the range of between 0,0106-1,2979 ppm. Therelation of correlation regression gondang and water has negative direction andcorrelation between gondang with sediment is positive direction.